2015
DOI: 10.12998/wjcc.v3.i2.132
|View full text |Cite
|
Sign up to set email alerts
|

Role of third molars in orthodontics

Abstract: The role of third molars in the oral cavity has been extensively studied over the years. Literature includes numerous diagnostic and treatment alternatives regarding the third molars. However, an issue that has not been discussed at the same level is their involvement in orthodontic therapy. The aim of this study is to present a review of the contemporary literature regarding the most broadly discussed aspects of the multifactorial role of third molars in orthodontics and which are of general dental interest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 56 publications
1
26
0
4
Order By: Relevance
“…15 On the other hand, Studies have suggested that factors like fixed orthodontic treatment which involves extraction of lower premolars followed by subsequent closure of residual spaces allowed the position of many impacted third molars to improve significantly by increasing the available space from 4 mm to 11 mm and decreasing the distance to the occlusal plane from 12 to 10 mm. 16 The minimum age of participants in this study was 20 years (mean: 29 ± 6 years). Growth of the jaws is basically completed by the age of 17 years 16 ; therefore at the age of 20, it is possible to distinguish whether a third molar is in normal eruptive process or will remain impacted in the jaw.…”
Section: Discussionmentioning
confidence: 99%
“…15 On the other hand, Studies have suggested that factors like fixed orthodontic treatment which involves extraction of lower premolars followed by subsequent closure of residual spaces allowed the position of many impacted third molars to improve significantly by increasing the available space from 4 mm to 11 mm and decreasing the distance to the occlusal plane from 12 to 10 mm. 16 The minimum age of participants in this study was 20 years (mean: 29 ± 6 years). Growth of the jaws is basically completed by the age of 17 years 16 ; therefore at the age of 20, it is possible to distinguish whether a third molar is in normal eruptive process or will remain impacted in the jaw.…”
Section: Discussionmentioning
confidence: 99%
“…30 Despite the fact that the role of third molars has been the subject of research, clinical interest, and debate for years, there is still a lack of scientific evidence from high-quality clinical studies on this subject. 42 However, Normando et al 43 suggest that, in general, the best clinical conduct is not to proceed with the prophylactic extraction of third molars, except in situations where removal of a third molar is mandatory from the beginning of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Zurzeit gibt es keine evidenzbasierte Studie, die ein prophylaktisches Entfernen gesunder impaktierter Weisheitszähne unterstützt. Ist jedoch eine Extraktion indiziert, sollte diese bevorzugt vor dem Erwachsenenalter durchgeführt werden, um das Risiko für Komplikationen gering zu halten [25].…”
Section: Frontzahn-crowding Und Prophylaktische Entfernung Von Weisheunclassified